2022
DOI: 10.1097/mco.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in human milk

Abstract: Purpose of reviewMilk-derived extracellular vesicles (MDEVs) are nanovesicles that carry microRNA (miRNA) DNA, RNA, proteins and lipids. MDEVs have a potential of therapeutic targets, based on their properties and cargo profile. The present review summarizes recent studies on MDEVs, their cargo and potential role in mammalian development. Recent findingsThe detailed characterization of their miRNA cargo leads to the conclusion of their potential importance in the regulation of gene expression, immune function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…from mothers to breastfeeding infants. [1,7,16,36,37] Maternal health conditions influence the composition of HM exosomes and may further change the functionalities of HM exosomes. Results in this study and others [18] indicate that GDM changes the miRNA profiles in HM exo-somes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…from mothers to breastfeeding infants. [1,7,16,36,37] Maternal health conditions influence the composition of HM exosomes and may further change the functionalities of HM exosomes. Results in this study and others [18] indicate that GDM changes the miRNA profiles in HM exo-somes.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Since then, increasing interest have been ignited in scientific community regarding the HM exosomes, its cargoes and their functionalities. [1,7] Studies have shown that HM exosomes can modulate infantile immune system and influence infant growth and health. [8] Recently, Melnik et al proposed that HM exosomes should be considered as signalosomes derived from the maternal lactation genome emitted to promote growth, maturation, immunological and metabolic programming of the offspring, [8] boosting the confidence and further desire of scientists on exploring the bioactivities of HM exosomes as well as its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are endosomal membrane-derived vesicles, approximately 50–150 nm in size, formed during endocytosis and secreted by almost all types of cells, and are present in large numbers in body fluids such as blood, urine, cerebrospinal fluid, tears, and saliva. Their main constituents are lipids, proteins, and nucleic acids, including microRNAs (miRNAs), messenger RNA (mRNA), and DNA derived from secretory cells transferred to other cells [ 12 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ,…”
Section: Introductionmentioning
confidence: 99%
“…EVs encompass a heterogeneous population of particles including microvesicles, which are assembled and released from the plasma membrane, and exosomes that are of endosomal origin and released by exocytosis of multivesicular bodies [ 2 , 3 ]. EVs are released essentially by all types of cells and can be isolated from the supernatant of cell and tissue cultures [ 4 , 5 ], as well as most body fluids, such as breast milk [ 6 ] and urine samples [ 7 ]. Initially thought of exclusively as cell disposal bags, EVs are now known as a regulated means of communication over short and long distances between cells and tissues [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%